Inhibitory Control Skills and Language Acquisition in Toddlers and Preschool Children. Issue 3 (22nd January 2020) - Gandolfi, Elena; Viterbori, Paola
Abstract: In this study, we explored the role of emerging inhibitory control skills in language acquisition in 62 typically developing children aged 24–32 months and investigated whether early inhibitory control skills are longitudinally associated with language outcome. Specifically, we focused on two different inhibitory processes that develop approximately at age 3, namely, response inhibition and interference suppression. At Time 1 children were administered five inhibitory control tasks and a language test; language abilities were also evaluated by means of a parent‐report questionnaire. Receptive morphosyntactic ability was assessed after 1 year (Time 2) in a subsample of 28 children. Hierarchical multiple linear regression analysis showed that all language production measures at Time 1, as well as later receptive morphosyntactic ability at Time 2, were significantly associated with the interference suppression score, even when early lexical and grammatical measures, age, and mother's education were included in the analysis. Abstract :